المقاصد القرآنية لسورة الجن - بوغزالة, وهيبة (University of eloued جامعة الوادي, 2021)
"ملخص البحث باللغة العربية: تهدف هذه الدراسة الموسومة بــ: -المقاصد القرآنية لسورة الجن- إلى بيان لمقاصد التي اشتملت عليها سورة الجن، وذلك من خلال تعريف المقاصد وبيان أهميتها، ومن ثم التطرق إلى أقسامها ومجالاتها، ثم تعريف عام بسورة الجن مدرجة تحته مقاصد السورة العامة، ثم محورها الأساس ومناسباتها، ثم قمت بدراسة مقاصد سورة الجن من خلال تقسيمها إلى أربعة مقاطع، وجعلت لكل مقطع مطلباً وعنواناً، ثم ذكرت مناسبة الآيات، وسبب النزول، والمعنى الإجمالي للآيات، وموضوع ومقاصد الآيات، وما ترشد إليه، وأخيرا ربط الآيات بالواقع. وتوصلت في نهاية هذه الدراسة إلى نتائج أهمها: اشتمال سورة الجن على مقاصد عظيمة وهي: استماع الجن للقرآن الكريم وتأثرهم به، والجن ورحلة الإيمان، ومعرفة الله تعالى بالغيب وإحاطته بمعرفة جميع ما في الكائنات. ""Summary: This study, tagged with: The Qur’anic purposes of Surat Al-Jin, aims to elicit the purposes included in Surat Al-Jin, by defining the purposes and clarifying their importance, and then addressing its sections and fields, then a general definition of Surat Al-Jinn, under which are the general purposes of the surah, then its main focus. Then I studied the purposes of Surat Al-Jin by dividing it into four sections, and made each section a demand and a title, then I mentioned the occasion of the verses, the reason for revelation, the overall meaning of the verses, the subject and purposes of the verses, and what they guide to, and finally linking the verses to reality. At the end of this study, I reached the most important results: Surat Al-Jinn includes great purposes, namely: the jinn’s listening to the Holy Qur’an and their influence on it, the jinn and the journey of faith, God Almighty’s knowledge of the unseen and his knowledge of all that is in beings "
مذكرة ماستر تخصص علوم قرآن
Keywords: المقاصد القرآنية، عالم الجن، إيمان الجن بالوحي; Quranic purposes, the world of the jinn, the belief of the jinn in revelation.